The Contrast of Toxic Parenting in Standard Child-Raising Patterns in Qs. Luqman Verses 13-19 from a Modern Interpretation Perspective - ramadanta (Noor: Journal of Islamic Studies, 2025)
This study examines the issue of toxic parenting that has emerged recently. Parents who do not have ideal and relevant parenting standards will have a negative impact on children. This problem will be examined from a religious perspective, how religion addresses the issue of toxic parents and what solutions it will offer, especially in the context of the Qs. Luqman verses 13-19, and what forms of toxic parenting are seen from the perspective of the Qs. Luqman verses 13-19. The method used to explore this problem is qualitative research using library sources such as articles, journals, and books as data. From this study, it was found that the ideal parenting standard according to the Qs. Luqman verses 13-19 is a parenting pattern that uses an interactive approach, parents as role models, and instills religious education in children. Conversely, if parents do not implement these basic parenting standards, it will have a negative impact on children in terms of mental health, thought patterns, and deviant behavior.